EFISIENSI BIAYA LAYANAN MELALUI INOVASI KEBIJAKAN BERBASIS TEKNOLOGI DI RUMAH SAKIT MARGONO PURWOKERTO - Ningtyas, Trimurti; Minhando, Erys Al Fauzi; Lestari, Asih Widi; Mutafarida, Binti (UIN Sayyid Ali Rahmatullah, 2021)
Public policy is the focus of attention in an effort to improve the service quality of public sector organizations. Policy innovation provides an offer for the development of policy studies to continuously improve their quality in order to improve organizational performance. This study aims to identify innovations in health service policies at Margono Hospital so that they can improve the quality of service of the organization. Using qualitative methods with descriptive analysis, this study tries to describe and explain the existence of these policy innovations. As a result, there are five types of innovation, namely process innovation, product innovation, method innovation, system innovation and conceptual innovation. The five innovations provide each progress for improving service performance in hospitals. Margono